International Outsourcing and Wage Rigidity: A Formal Approach and First Empirical Evidence - Daniel Horgos (FIW - Research Centre International Economics, 2009)
International Outsourcing effects on labor markets are mostly analyzed within flexible wage settings. Using a modern duality approach, this paper formally investigates differences occurring in industries with low skilled wage rigidity and, for the first time in literature, presents empirical evidence supporting the theoretical findings. Using a logit model to analyze microeconomic German panel data, results show that International Outsourcing significantly increases low skilled unemployment when taking place in industries characterized by low skilled wage rigidity. Thus, in terms of unemployment, not International Outsourcing but inflexible labor market institutions instead should be blamed for harming low skilled labor.
Keywords: F12; J64; F41; 330; International Outsourcing; Wage Rigidity; Unemployment